(3GdahGFO aj CMGOjK GdCMcGes - (3CHh GdMSf YdGA GdOjf Ydj Hf YKeGf Hf EHQGgje Hf GdJQceGfj GdeGQOjfj,J (B750 (3g` s ((3MSf Hf jhSa HGTG s)
(3ChdgG (B:s
(3bGd HjGf GdSHjd PcQ ajg MOKfG Yf GHf YeQ ai SfOg EHQGgje GdLhRi Ke bGd (B: (3hgPG TGgO dMOjK GdLhRi s
(3BNQgG (B:s
(3bdJ PcQ gPg GdeSCdI (B( (3eSCdI GdYRd Yf GdLGQjI (B) (3ai gPG GdHGH ZjQ efGSH hbO PcQgG Gdjgbi ajeG JbOe ai ChGNQ CHhGH GdYOI Je GdcJGH s
(3GdfSNI HgG MhGTs
(3hbO CJe GdeDda JCdjag SfI (B747(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B311s
Keywords: (3GdMOjK h GdeUWdMs